Conditional targeting in mice reveals that hepatic homogentisate 1, 2-dioxygenase activity is essential in reducing circulating homogentisic acid and for effective therapy in the genetic disease alkaptonuria. (10th October 2019) - Hughes, Juliette H; Liu, Ke; Plagge, Antonius; Wilson, Peter J M; Sutherland, Hazel; Norman, Brendan P; Hughes, Andrew T; Keenan, Craig M; Milan, Anna M; Sakai, Takao; Ranganath, Lakshminarayan R; Gallagher, James A; et al.
Abstract: Alkaptonuria is an inherited disease caused by homogentisate 1, 2-dioxygenase (HGD) deficiency. Circulating homogentisic acid (HGA) is elevated and deposits in connective tissues as ochronotic pigment. In this study, we aimed to define developmental and adult HGD tissue expression and determine the location and amount of gene activity required to lower circulating HGA and rescue the alkaptonuria phenotype. We generated an alkaptonuria mouse model using a knockout-first design for the disruption of the HGD gene. Hgd tm1a −/− mice showed elevated HGA and ochronosis in adulthood. LacZ staining driven by the endogenous HGD promoter was localised to only liver parenchymal cells and kidney proximal tubules in adulthood, commencing at E12.5 and E15.5 respectively. Following removal of the gene trap cassette to obtain a normal mouse with a floxed 6 th HGD exon, a double transgenic was then created with Mx1-Cre which conditionally deleted HGD in liver in a dose dependent manner. 20% of HGD mRNA remaining in liver did not rescue the disease, suggesting that we need more than 20% of liver HGD to correct the disease in gene therapy. Kidney HGD activity which remained intact reduced urinary HGA, most likely by increased absorption, but did not reduce plasma HGA nor did it prevent ochronosis. In addition, downstream metabolites of exogenous 13 C6 -HGA, were detected in heterozygous plasma, revealing that hepatocytes take up and metabolise HGA. This novel alkaptonuria mouse model demonstrated the importance of targeting liver for therapeutic intervention, supported by our observation that hepatocytes take up and metabolise HGA.